Ali Yaycioglu, Partners of the Empire: The Crisis of the Ottoman Order in the Age of Revolutions - Gara, Eleni (Historein, 2019)
Review of Ali Yaycioglu. Partners of the Empire: The Crisis of the Ottoman Order in the Age of Revolutions. Stanford: Stanford University Press, 2016. 347 pp.